Women in the Feminist Struggle During the Pre-Independence Period - Rosida, Anisatur (CV. Sekawan Siji, 2024)
The topic of the role of women has always been an ongoing discussion. When viewed from a global perspective, the Indonesian women's movement is one of the movements that occur in many other countries. Since before independence until today, the Indonesian women's movement has a long history. Women as domestic workers and their role in the public sphere continue to be debated and discussed everywhere. One of them is related to the women's movement. The main goal of movements founded by women activists is to improve the status of women. At some point in history, Indonesian female figures have contributed to women's struggle for social justice and humanity. This shows that Indonesian women really laid the foundation of the women's movement.